2022
DOI: 10.1039/d1dt02908h
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the electron transfer pathway in photodynamic activity of Ru(ii) polypyridyl complexes containing 4,7-diphenyl-1,10-phenanthroline ligands under normoxic and hypoxic conditions

Abstract: The purpose of this study was to investigate a correlation between the spectroscopic and photophysical properties of Ru(II) polypyridyl complexes and their photodynamic activity in vitro. A series of Ru(II)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 69 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…Several studies have demonstrated this oxygen-independent photochemistry in hypoxia under cell-free conditions, , and examples of phototoxic responses toward cancer cells growing in hypoxia are starting to emerge. Reliable strategies for maintaining hypoxia and assessing the dissolved oxygen concentration at the time of illumination have proven difficult but are now beginning to materialize, ,, , making it possible to examine the potential of PCT agents as hypoxia-active phototherapeutics. In collaboration with the Glazer group, we published the most active PCT agent (at the time)with [Ru­(6,6′-dmb) 2 (1-NIP)]­Cl 2 and a phototherapeutic index (PI) of 15 (ratio of dark to light EC 50 values) at 1% O 2 using visible light, where 1-NIP is 2-(naphthalen-1-yl)-1 H -imidazo­[4,5- f ]­[1,10]­phenanthroline. , Bonnet and co-workers have since achieved a PI near 16 under 1% O 2 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated this oxygen-independent photochemistry in hypoxia under cell-free conditions, , and examples of phototoxic responses toward cancer cells growing in hypoxia are starting to emerge. Reliable strategies for maintaining hypoxia and assessing the dissolved oxygen concentration at the time of illumination have proven difficult but are now beginning to materialize, ,, , making it possible to examine the potential of PCT agents as hypoxia-active phototherapeutics. In collaboration with the Glazer group, we published the most active PCT agent (at the time)with [Ru­(6,6′-dmb) 2 (1-NIP)]­Cl 2 and a phototherapeutic index (PI) of 15 (ratio of dark to light EC 50 values) at 1% O 2 using visible light, where 1-NIP is 2-(naphthalen-1-yl)-1 H -imidazo­[4,5- f ]­[1,10]­phenanthroline. , Bonnet and co-workers have since achieved a PI near 16 under 1% O 2 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, PDT can induce hypoxia as oxygen is consumed during irradiation. , Decreased generation of ROS limits damage to cancerous cells. To address this, there is motivation to develop light-triggered compounds that exploit oxygen-independent mechanisms for phototoxicity. In this context, metal complexes such as Ru(II) polypyridyl systems have attracted considerable attention. ,,, Judicious choice of ligand–metal combinations provides access to a variety of excited-state configurations with characteristic photophysical properties and reactivities. Strategies have included photorelease of bulky ligands to reveal phototoxic metals and/or ligands, ,,,,, photocaging of chemotherapeutics and enzyme inhibitors, ,,,,, …”
Section: Introductionmentioning
confidence: 99%
“…The potential luminescence of Ru(bpy)-based units did not exhibit any appreciable emission in complexes C5 and C6 , which was attributed to the intramolecular quenching of the Ru-bpy luminescence by the Os( ii ) center. 35,53 The above comparison suggested that the energy transfer occurred within the Os( ii )/Ru( ii ) binuclear complexes. 18,53,54 Φ c = ( I c / I s )( A c / A s )( η c 2 / η s 2 ) Φ s where c and s stand for the compounds of synthesized and standard complex, η is the refractive index of the solvent, A is the solution absorbance at the excitation wavelength ( λ ex ), I is the integrated emission intensity, and Φ s is the standard luminescence quantum yield of [Ru(bpy) 3 ] 2+ ( Φ = 0.06).…”
Section: Resultsmentioning
confidence: 90%
“…2, and the corresponding data are listed in Table 1. 35 Complexes C1 , C2 , C3 , and C4 presented three absorption bands, whereas C7 and C8 only showed two absorption bands. However, the heterometallic complexes C5 , C6 , C9 , and C10 exhibited four absorption bands in the range of 200–800 nm.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation